2021
DOI: 10.1111/imig.12900
|View full text |Cite
|
Sign up to set email alerts
|

Origin and transit migration of Afghans and Syrians to Germany: The influential actors and factors behind the destination choice

Abstract: We use Process Net‐Maps to visualize the irregular migration patterns of refugees and identify influential actors/factors shaping their decisions. A qualitative case study was used that included 87 Afghan and Syrian refugees (52 individual in‐depth interviews and 35 participants in five focus group discussions) residing in Stuttgart, Germany. Results show a typical pattern for respondents to first migrate to a neighboring country, and then a mixture of decisive factors induce them to migrate onward. The perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Brekke and Aarset, 2009;Collyer, 2004;Glorius and Nienaber, 2022). For others, their families made the decision about their destination (Brekke and Aarset, 2009;McAuliffe, 2017;McAuliffe and Jayasuriya, 2016;Torfa et al, 2022;Zimmermann, 2010). Torfa et al (2022) found that the chief decision-maker can also change at different stages in migration journeys.…”
Section: Intervening Obstacles Personal Factors and Limits To Decisio...mentioning
confidence: 99%
See 3 more Smart Citations
“…Brekke and Aarset, 2009;Collyer, 2004;Glorius and Nienaber, 2022). For others, their families made the decision about their destination (Brekke and Aarset, 2009;McAuliffe, 2017;McAuliffe and Jayasuriya, 2016;Torfa et al, 2022;Zimmermann, 2010). Torfa et al (2022) found that the chief decision-maker can also change at different stages in migration journeys.…”
Section: Intervening Obstacles Personal Factors and Limits To Decisio...mentioning
confidence: 99%
“…Even where countries of first asylum were intended as destinations, poor conditions, the inability to make a living and a lack of safety can lead to onward migration aspirations (Crawley, 2010;Crawley and Hagen-Zanker, 2019;Glorius and Nienaber, 2022;Kuschminder and Waidler, 2020;Müller-Funk, 2019;Zimmermann, 2010). On the other hand, integration and access to rights in countries of first asylum, the perception of closer cultural affinities, the hope of return, the ability to remain close to family, employment and easier access to labour markets can increase aspirations to stay (Müller-Funk, 2019;Torfa et al, 2022).…”
Section: Countries Of First Asylummentioning
confidence: 99%
See 2 more Smart Citations
“… “The term “asylum seeker” refers to those whose asylum applications are still under review and, “refugee” is used as a general term for persons with different types of protection status.” (Torfa et al, 2022 p.17). …”
mentioning
confidence: 99%